Altered resting-state regional homogeneity after 13 weeks of paliperidone injection treatment in schizophrenia patients. (30th December 2016) - Bai, Yan; Wang, Weixin; Xu, Jian; Zhang, Fengrui; Yu, Hongjun; Luo, Chunrong; Wang, Lianzhang; Chen, Xianyu; Shan, Baoci; Xu, Lin; Xu, Xiufeng; Cheng, Yuqi
Abstract: This study aimed to explore the effects of the long-acting antipsychotic drug palmitate paliperidone in resting-state brain activity of schizophrenia patients. Seventeen schizophrenia outpatients were included and received palmitate paliperidone injection (PAL) treatment for 13 weeks. These patients were compared to seventeen matched healthy controls. All subjects underwent two scan sessions of resting-state magnetic resonance imaging (baseline and the 13th week) and regional homogeneity (ReHo) at resting-state where compared. After 13 weeks of treatment, PAL increased ReHo of the prefrontal cortex, anterior cingulate gyrus and orbital frontal gyrus, while PAL decreased ReHo of the thalamus, parahippocampal gyrus and superior temporal gyrus. Furthermore, improvement of psychiatric symptoms correlated with changing amplitude of ReHo: positively correlated with postcentral gyrus and negatively correlated with the occipital cortex. Baseline ReHo values of the middle occipital gyrus were positively correlated with the rate of reduction of psychiatric symptoms and improvement of social function. These results suggested that PAL might achieve its clinical effect in schizophrenia by influencing the resting-state function of the occipital cortex, lateral prefrontal cortex and temporal lobe. Baseline function of the inferior occipital gyrus might potentially predict the short-term effect of PAL in schizophrenia. Highlights: This is a prospective study observing the effect of long-acting antipsychotics in schizophrenia. Antipsychotics can change the abnormal resting state activities in schizophrenia. Psychiatric symptom improvement is found correlated with the change amplitude of ReHo values in schizophrenia.